METHODOLOGY FOR USING THE FLIPPED CLASSROOM METHOD IN THE DEVELOPMENT OF WRITING SKILLS OF STUDENTS OF THE ECONOMICS DIRECTION IN ENGLISH - Maqsudova Hilola PhD; Kunaboyev Shoxrux Bahodirovich (Western European Studies, 2024)
This article explores the implementation of the Flipped Classroom methodology as a transformative approach to enhancing the writing skills of economics students in an English-language context. Through a comprehensive examination of literature, methodologies, and results, the article provides valuable insights into the effectiveness of the Flipped Classroom model in developing critical writing abilities among students pursuing economics education
Keywords: Flipped classroom; writing skills; economics students; english language